2020
DOI: 10.1002/ece3.6623
|View full text |Cite
|
Sign up to set email alerts
|

Macroevolutionary integration of phenotypes within and across ant worker castes

Abstract: Phenotypic traits are often integrated into evolutionary modules: sets of organismal parts that evolve together. In social insect colonies, the concepts of integration and modularity apply to sets of traits both within and among functionally and phenotypically differentiated castes. On macroevolutionary timescales, patterns of integration and modularity within and across castes can be clues to the selective and ecological factors shaping their evolution and diversification. We develop a set of hypotheses descr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 101 publications
(165 reference statements)
3
17
0
Order By: Relevance
“…In many ways, the study of parasite-induced phenotypes thus overlaps with ongoing investigations of caste evolution and development (e.g., [ 10 , 11 , 173 175 ]), with developmental timing and environmental factors playing key roles in both lines of research. In the cases reviewed herein, the presence of the parasite may take on the role of a developmental cue and shift the host onto a different ontogenetic trajectory, depending on the timing and severity of the infection [ 30 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many ways, the study of parasite-induced phenotypes thus overlaps with ongoing investigations of caste evolution and development (e.g., [ 10 , 11 , 173 175 ]), with developmental timing and environmental factors playing key roles in both lines of research. In the cases reviewed herein, the presence of the parasite may take on the role of a developmental cue and shift the host onto a different ontogenetic trajectory, depending on the timing and severity of the infection [ 30 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the pupa of holometabolous insects represent a closed system, previous authors have interpreted a parasite present during this developmental phase as a foreign tissue that may compete for resources with the host’s growing organs or influence the coordinated growth of imaginal structures [ 10 , 86 ]. The resulting phenotypes often highlight not only the apparent plastic response of the host but also the remarkable robustness and modularity of ant development under environmental perturbation: previous studies [ 12 , 53 , 173 , 174 ] have found ant body plans to be highly modular, i.e. while certain structures are tightly correlated through ontogeny and function, they are relatively independent of other such character clusters [ 176 , 177 ].…”
Section: Discussionmentioning
confidence: 99%
“…The morphological evolution of Pheidole might be strongly driven by differences in size (Pie & Traniello, 2007), which tends to evolve at higher rates than shape (Pie & Tschá, 2013; Economo et al, 2015a; Friedman et al, 2019). More recently, studies applying geometric morphometric approaches validated the prominence of size to explain the morphological disparity in the genus but also pointed to different evolutionary rates and levels of integration between head and mesosoma shape and size (Friedman et al, 2019; 2020). Pheidole morphological diversification seems to be very constrained (Pie & Traniello, 2007), in contrast to their ecological disparity (Economo et al, 2015a; 2015b), as reflected in the widespread distribution of genus throughout most of the terrestrial ecosystems (Economo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the main trends in the morphological evolution of Pheidole received considerable attention in the past decade, with different approaches being employed to understand the evolution of a wide variety of structures, showing contrasting results to the relative contributions of size and shape to the morphological diversity of the genus (Pie & Traniello, 2007; Pie & Tschá, 2013; Sarnat et al, 2017; Friedman et al, 2019; 2020), yet little is known about the evolution of mandibular morphology in Pheidole . Ants have a typical pterygote mandible with two articulations with the head (Snodgrass 1935), the dorsal and ventral mandibular joints (Richter et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the main trends in the morphological evolution of Pheidole has received considerable attention in the past decades. Different approaches were employed to understand the evolution of a variety of structures, showing contrasting results to the relative contributions of size and shape to the morphological diversity of the genus [23,[25][26][27][28]. However, little is known about the evolution of mandibular morphology in Pheidole.…”
Section: Introductionmentioning
confidence: 99%